Understanding School Belonging: Its Role in Enhancing Student Well-Being and Motivation - Xiong, Lu; Mu, Ye; Motevalli, Saeid; Bt A Razak, Rogayah (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: School belonging, characterized as students' emotional attachment and acceptability within educational environments, is crucial for their subjective well-being and motivation. This idea profoundly impacts life satisfaction, positive and negative affect, and general mental health. Despite growing acknowledgment of its significance, a comprehensive examination of the relationship among school belonging, subjective well-being, and motivation is still few.Methods and Materials: This analysis synthesizes information from longitudinal studies, surveys, and cross-sectional analyses across multiple educational environments to elucidate the complex interactions among these dimensions.Findings: The findings demonstrate that a strong sense of belonging markedly improves students' subjective well-being, motivation, life satisfaction, and better mental health. A supportive school atmosphere cultivates a sense of acceptability and worth, hence enhancing students' intrinsic motivation and participation in academic endeavors. Programs designed to augment emotional support and inclusivity significantly enhance subjective well-being and academic achievement. Fostering a robust sense of belonging is essential for enhancing students' educational experiences.Conclusion: These insights underscore the necessity for educational institutions to establish comprehensive programs that foster a sense of belonging, thereby improving students' subjective well-being and motivation. Addressing these factors is essential for cultivating a supportive educational climate that allows all students to excel intellectually and psychologically.